Improving the Economy and Industrial Development of MSMEs with Motivation as an Intervening Variable in Communities in Aceh Province - Fuandri Fuandri; Syaifuddin Syaifuddin; Nagian Toni (CV. Aksara Global Akademia, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in improving the regional economy and the economy of a country. Because the increase in MSMEs is considered to be a solution to overcome the economy. Data collection method in this study using Quantitative.Therefore, this study will examine the impact of economic improvement policies and industrial development on MSMEs in Aceh Province. The results of the study show that the policy of increasing the economy has a very large influence on the progress of UMKM in Aceh Province. Likewise, industrial development also has a very large influence on the development of MSMEs in Aceh Province. So it can be concluded that the existence of policies to increase the economy and industrial development have enormous influence and benefits on the economic progress of Aceh Province..